Exploring Students' Strategies to Solve Ordinary Differential Equations in a Reformed Setting - Habre, Samer (2000)
The undergraduate curriculum in ordinary differential equations (ODEs) has undergone some important changes in favor of the visual and numerical aspects of the course. However, research findings of the effects of this reform on student thinking are still minimal. This article examines whether students consider slope (or direction) fields as a means for solving first-order ODEs and studies students' success in reading information from these fields. It also investigates students' abilities converting symbolic information into graphical ones and vice-versa. The setting is a third-semester college calculus course where the visual approach was highly emphasized; also, computers were an integral part of the instruction process.